P232 The relationship between respiratory muscle mechanomyogram activity and breathlessness in chronic obstructive pulmonary disease. (December 2018) - Estrada, L; Lozano-García, M; Moore, A; Cho, PSP; Newlove, K; Paulson, S; Torres, A; Sarlabous, L; Rafferty, GF; Moxham, J; Jané, R; Jolley, CJ
Abstract : Introduction: Breathlessness is a dominant, distressing, symptom of chronic obstructive pulmonary disease (COPD) which has a significant impact on quality of life. Neural respiratory drive (NRD), quantified as diaphragm electromyogram (EMGdi) activity, is closely related to breathlessness intensity in COPD. The surface mechanomyogram (sMMG), which can be recorded using skin-surface triaxial accelerometers, measures the lateral vibration of muscle fibres and is considered to be the mechanical counterpart of the surface EMG (sEMG). The principal aim of this study was to investigate the relationship between the sMMG of the diaphragm (sMMGdi) and breathlessness in COPD. We hypothesised that there would be strong positive relationships between sMMGdi and modified Borg (mBorg) breathlessness intensity during an inspiratory threshold loading protocol. Methods: Nine COPD patients (7 male, median (IQR) age 70 (64–78) years, BMI 25.6 (24.8–30.1) kg/m 2, FEV1 44.7 (37.1–63.9)%predicted), underwent an incremental inspiratory loading protocol at 12%, 24%, 36%, 48% and 60% of maximum mouth inspiratory pressure (PImax). Left and right sEMGdi and sMMGdi activity were recorded using 2 pairs of sEMG electrodes, and one pair of triaxial accelerometers, positioned over the 7th/8th intercostal spaces in the anterior axillary lines bilaterally. sEMG and sMMG signals were analysed using fixed sample entropy (fSampEn) and the relationships with mBorg breathlessness intensity during each inspiratory load were determined using correlation analysis. Results: Moderate to strong correlations were observed between mBorg breathlessness intensity and the sEMG and sMMG signals, expressed as fSampEn, recorded at all sites (table 1). Conclusion: The relationships observed between mBorg breathlessness intensity and sMMGdi, and sEMGdi, expressed as fSampEn, demonstrates the potential value of sMMGdi as a complementary tool to sEMGdi for the investigation of breathlessness in COPD. sMMGdi could provide a novel non-invasive physiological correlate of breathlessness intensity in COPD and other chronic respiratory diseases.